Money, Indenture, and Neo-slavery in the Spanish Gulf of Guinea, 1820s to 1890s - Martino, Enrique (Comparativ, 2021)
This article looks for the initial configuration of indentured labour in the final stages of the Spanish Empire in the Gulf of Guinea to try to give, from this peculiar historical trajectory, a new spin on the concept of transition, or rather transformation, from slavery to post-slavery forms of unfree labour. The first labour contract in the Spanish colonial island of Fernando Pó, sitting off the coast of Nigeria and Cameroon, was brought over in the 1860s from Cuba, which combined both coolie indentures and emancipado (apprenticeships for slaves freed from slave ships) arrangements. I outline some of the emergent effects of this new colonial contract, such as the appearance of a new generation of labour recruiters by describing and examining the techniques used to try to attract and keep West African Kru workers on the island. By closely connecting Fernando Pó to the process of abolition of slavery in Cuba and to labour recruitment along the West African coast, I show how the founding and the effects of the contract can be tracked back to the partial fragmentation and mutation of slavery. I provide a conceptual outline in the conclusion in relation to a critical discussion of the metaphors of the “slavery of wage labour” and the sometimes just implicitly lingering premises of the concept of imperfect and inhibited transitions still underpinning much of the global labour history and the new histories of capitalism literature.